Leadership transition, ally restraints, and target state resistance - Qi, Haixia; Wang, Qi; Li, Ruoxing (Frontiers in Political Science, 2025)
Understanding how target states respond to international provocations is crucial to the study of crisis management and conflict onset. The primary focus of existing research is on the individual effects of ally influence and domestic politics without considering their interaction. This study addresses this gap by exploring the combined impact of leadership transitions, manners of leader entry, and ally’s importance on target states’ decisions to resist challenges. Utilizing the Truly Dyadic Dyad-Year (TDD) version of the Militarized Interstate Confrontation (MIC) dataset from 1920 to 2014, the Archigos leadership dataset, and logit models for statistical testing, our findings reveal that target states’ leadership transitions and irregular means of leaders entry significantly increase the likelihood of target states’ resistance, particularly when leaders seek to consolidate power. Moreover, although the support of a powerful ally may embolden the target state to resist, the restraining effect of allies during the target state’s leadership transitions becomes more pronounced. Our research highlights the intricate balance between domestic political considerations and external influences, emphasizing that an understanding of the domestic political context is essential for comprehending how states respond to international provocations and the effectiveness of ally restraints.